Parent’s Socioeconomics and Motivation for Continuing Education: Case Study of SMA Negeri 3 Tapung Hulu - Br Panjaitan, Istiqomah; Almasdi Syahza; Brilliant Asmit (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to determine the effect of parents' socio-economic conditions on the motivation to continue the education of high school students Negeri 3 Tapung Hulu.This research uses descriptive research with a Quantitative approach. The population was 550 students from grades X-XII. Using simple random sampling technique and the slovin formula, the sample size was 85 students and the data was obtained using a questionnaire.analysis of the effect of parents' socioeconomic conditions on motivation to continue education using simple linear regression analysis. The results showed that most parents had low or very low socioeconomic levels, which had a significant impact on the living conditions and development of their children. The level of student motivation is in the medium and high categories. The results of simple linear regression analysis show that parents' socioeconomics has a positive and significant influence on the variable of students' motivation to continue their education. Thus, parents' socioeconomic conditions have a positive impact on students' motivation to continue their education, and this is in accordance with the view that families with a good socioeconomic background can support their children's education. Conversely, families with poor socioeconomic backgrounds are more likely to carefully consider their children's education because they are more focused on the needs of their lives.